2023
DOI: 10.3390/su15043039
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Continuance Intention of Omnichannel: Combining TAM and TPB

Abstract: Nowadays, consumers use information devices to use products and services through various channels. Omnichannel promotes sales improvement by allowing businesses to secure multiple channels. It provides consumers with a wider range of choices and monetary advantages. As such, omnichannel facilitates economic sustainability as a major platform for commerce. The purpose of this study is to identify the determinants of consumers’ continuous intention to use omnichannel. This research collected data from 262 consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 90 publications
(136 reference statements)
1
4
0
Order By: Relevance
“…Considering the TPB part of the integrated model in this research, subjective norms caused significant impacts and PBC caused an insignificant effect on online purchase intention. The significant impact of SN is agreeable with the results from several authors (Song & Jo, 2023; Wang et al, 2016). This meant that individual online purchase intention was affected by the important surrounding persons.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Considering the TPB part of the integrated model in this research, subjective norms caused significant impacts and PBC caused an insignificant effect on online purchase intention. The significant impact of SN is agreeable with the results from several authors (Song & Jo, 2023; Wang et al, 2016). This meant that individual online purchase intention was affected by the important surrounding persons.…”
Section: Resultssupporting
confidence: 93%
“…In practice, authors integrated the TPB and TAM to better explain online purchase intention (German Ruiz-Herrera et al, 2023;Pen˜a-Garcı´a et al, 2020;Rehman et al, 2019;Singh, 2015;Song & Jo, 2023). Song and Jo (2023) and Rehman et al (2019) combined the TPB and TAM in a way that input factors of the TPB and TAM directly influenced purchase intention in the model. However, the TAM inputs showed unstable impacts on purchase intention.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, considering that both models have some degree of explanatory limitations, the TPB-TAM integrated model demonstrates greater explanatory power than either model alone. Song et al [31] and Lee et al [32] have achieved better results by using this integrated model in related research. In addition, this integrated model served as a customer relationship…”
Section: An Integrated Model Of Tpb and Tammentioning
confidence: 93%
“…Moreover, considering that both models have some degree of explanatory limitations, the TPB-TAM integrated model demonstrates greater explanatory power than either model alone. Song et al [31] and Lee et al [32] have achieved better results by using this integrated model in related research. In addition, this integrated model served as a customer relationship management (CRM) tool to establish effective channels and methods of owner-centered information management, helping to promote the growth and future development of BIM technology.…”
Section: An Integrated Model Of Tpb and Tammentioning
confidence: 93%
“…They revealed how usage intention is positively affected by facilitating conditions and personal innovativeness. Song and Jo [66] integrated the TAM and theory of planned behavior (TPB) to examine the predictors of continuance intention of omnichannel users. The authors found that accessibility, monetary saving, and perceived risk affect continuance intention via relative advantage.…”
Section: Background and Related Workmentioning
confidence: 99%